Low-switching frequency modulation schemes for multi-level inverters - Kumar, A. Rakesh (Boca Raton, FL : CRC Press, 2021)
Multi-level Inverters (MLIs) are widely used for conversion of DC to AC power. This book provides various low-switching frequency (LSF) modulation schemes (conventional and improved), which can be implemented on MLIs. The LSF modulation schemes are implemented to three different MLI topologies to demonstrate their working and aimed at their application to reader invented MLI topologies. Highlighting the advantages of LSF over high-switching frequency (HSF) modulation schemes, the simulations are carried out using MATLAB/Simulink along with hardware experiments. The practical application of MLIs to renewable energy sources and electric vehicles is also provided at the end of the book. Aimed at researchers, graduate students in Electric Power Engineering, Power Electronics, this book: Presents detailed overview of most commonly used multi-level invertor topologies. Covers advantages of low-switching over high-switching frequency scheme. Includes an exclusive section dedicated for an improved low-switching modulation scheme. Dedicated chapter on application of renewable energy sources to multi-level invertors and electric vehicles. Explains all the low-switching frequency modulation schemes.
OCLC-licensed vendor bibliographic record.
Keywords: Electric inverters; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General